DULAC'S THEOREM - Benazic Tomé, Renato Mario (2009)
In this work is proven the Dulac's Theorem,whích establishes that if acomplex 2-dimension vector field, which linear part has two resonant eigenvectors in the Poincare domain then it is locally analytically conjugate to a polinomial vectorfield. Is is also studied the geometric behavior of its orbits in a neighborhood of asingularity.